Current learning strategies in fire evacuation for seniors and people with disabilities in private seniors’ residences and long-term care homes: a scoping review - Thériault, William; Blanchet, Guillaume; Vincent, Claude; Feillou, Isabelle; Ruel, Jean; Morales, Ernesto (Frontiers in Rehabilitation Sciences, 2024)
Current strategies for teaching evacuation methods in private seniors' residences (PSR) and longterm care (LTCH) homes may pose risks to people with disabilities (PWD) and seniors' physical and psychological health. This study aimed to address the following questions: 1) Which are the current fire evacuation learning strategies used with PWD or seniors? 2) What are the barriers and facilitators for PWD and seniors' during fire evacuation and learning strategies in PSR and LTCH? 3) What is the existing equipment that could be used with PWD seniors? A scoping review of grey and scientific literature was done in six databases and Google scholar. Additional information was found on Québec government websites. This review identified 13 scientific papers and 22 documents. Twenty barriers (personal=9, environmental=11), and 14 facilitators (personal=4, environmental=10) were extracted. The current fire evacuation learning strategies currently used can be grouped into three categories: drills; training; promotion of a fire safety plan. Six types of evacuation equipment were found; however, their use has been scarcely documented. Safety for seniors during fire evacuation is still an important issue to be improved. Increasing awareness and creating new practices and tools that consider the strengths and difficulties of seniors seems to be a promising avenue for improving evacuation.